2023
DOI: 10.3114/sim.2022.106.02
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of colacosome-interacting mycoparasites expands the understanding of the evolution and ecology of Microbotryomycetes

Abstract: Mycoparasites in Basidiomycota comprise a diverse group of fungi, both morphologically and phylogenetically. They interact with their hosts through either fusion-interaction or colacosome-interaction. Colacosomes are subcellular structures formed by the mycoparasite at the host–parasite interface, which penetrate the parasite and host cell walls. Previously, these structures were detected in 19 fungal species, usually by means of transmission electron microscopy. Most colacosome-forming species have been assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A third type is recognised as a regular placement of colacosomes in parasite hyphae coiling around host hyphae. So far, this type of arrangement has only been found in Colacogloea papilionacea and Slooffia micra (Kirschner & Oberwinkler 2001, Schoutteten et al 2023. A fourth type has been observed by Bauer (2004) in a yet undescribed colacosome-interacting mycoparasite of a Tulasnella host.…”
Section: Pucciniomycotina -Microbotryomycetesmentioning
confidence: 99%
See 4 more Smart Citations
“…A third type is recognised as a regular placement of colacosomes in parasite hyphae coiling around host hyphae. So far, this type of arrangement has only been found in Colacogloea papilionacea and Slooffia micra (Kirschner & Oberwinkler 2001, Schoutteten et al 2023. A fourth type has been observed by Bauer (2004) in a yet undescribed colacosome-interacting mycoparasite of a Tulasnella host.…”
Section: Pucciniomycotina -Microbotryomycetesmentioning
confidence: 99%
“…However, no DNA sequence data or ultrastructural data are available and it is questionable that these species have affinity to Cystobasidiomycetes. Schoutteten et al (2023) suggested that C. sebaceum is most likely a member of the genus Slooffia (Microbotryomycetes).…”
Section: Cystobasidalesmentioning
confidence: 99%
See 3 more Smart Citations